Automation of Synthesis of Structures, Systems Engineering Strategies for Production. (2016) - Kuznetsov, Andrey; Štefan, Václav
Abstract: The article describes an automated system of support of decision-making structures in the synthesis strategies of industrial engineering systems, based on the method of structural and technological complexity of produced parts. This paper critically evaluates various tool management approaches, identifying the operational tradeoffs and analyzing the models developed to address management decisions involving tooling. The evidence is clear that a lack of attention to structured tool management has resulted in the poor performance of many manufacturing systems. Plant tooling systems affect product design options, machine loading, job batching, capacity scheduling, and real-time part routing decisions. With increasing automation in manufacturing systems, there is a growing need to integrate tool management more thoroughly into system design, planning and control.